Capital Humano y Género en la Empresa - Siller, Jesús Francisco Mellado; Ruiz, Edith Reyes; Wong, Adriana Mendez (European Scientific Journal, ESJ, 2018)
The present paper of human capital research in different countries has beenmeasured by the satisfaction index in models of some latent variables, where in some countries it manifests in the dimensions of people and business or work. A sample of 243 subjects was obtained in the southern region of the state of Coahuila, in different companies in the city of Saltillo, Torreón and Ramos Arizpe. It is found in the analysis that apparently the gender difference is still high in companies in the southern region of the state of Coahuila, where women feel more differences in the jobs they perform within the company, for this it is advisable to carry out awareness-raising work in the area of internal marketing, so that there is a gender competitiveness.